2006
DOI: 10.1211/jpp.58.2.0007
|View full text |Cite
|
Sign up to set email alerts
|

Low molecular weight chitosan inhibits obesity induced by feeding a high-fat diet long-term in mice

Abstract: Three low molecular weight chitosans (molecular weight: 21, 46 and 130 kDa) obtained by enzymatic hydrolysis of a high molecular weight chitosan (average molecular weight: 650 kDa) had low viscosity and were water-soluble. The effects of these water-soluble chitosans on pancreatic lipase (in-vitro) and the elevation of plasma triacylglycerol concentration after the oral lipid tolerance test were examined in mice. The water-soluble 46-kDa chitosan was the most effective at inhibiting pancreatic lipase activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
90
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(97 citation statements)
references
References 30 publications
6
90
0
1
Order By: Relevance
“…Chitosan, a biopolymer of glucosamine, is produced by the deacetylation of chitin and consists of polymers with various molecular weights. The hypolipidemic activity of chitosan is related to a number of chemical characteristics, including molecular weight, degree of acetylation and viscosity (6,27). Regarding the effect of the differential molecular weight, feeding an obese mouse model a HFD showed that chitosan with 46 kDa molecular weight is more effective at attenuating body weight gain and lowering blood total triglycerides and total cholesterol and LDL-cholesterol than 650 kDa chatoyant (6).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Chitosan, a biopolymer of glucosamine, is produced by the deacetylation of chitin and consists of polymers with various molecular weights. The hypolipidemic activity of chitosan is related to a number of chemical characteristics, including molecular weight, degree of acetylation and viscosity (6,27). Regarding the effect of the differential molecular weight, feeding an obese mouse model a HFD showed that chitosan with 46 kDa molecular weight is more effective at attenuating body weight gain and lowering blood total triglycerides and total cholesterol and LDL-cholesterol than 650 kDa chatoyant (6).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that chitosan and its oligomers display a variety of biological activities, including antitumor, hypoglycemic, hypolipidemic, antibacterial and eight control effects (1)(2)(3)(4)(5). The effectiveness of chitosan in lowering blood lipids and in body weight control allows it to decrease the risk of cardiovascular disease (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, their efficacy for weight loss is highly controversial, and in a survey of the literature reports are found for both confirmation and denial of this property. Conflicting results were obtained in in vivo experiments with humans and mice where chitosan was used as supplement in diets, with no or very little weight loss in some studies [8][9][10][11][12], whereas in other studies chitosan was able to inhibit increases in body weight [13,14].…”
Section: Introductionmentioning
confidence: 99%